Computer simulation of cardiac electrical activity using an electrocardiograph on; Неразрушающий контроль: электронное приборостроение, технологии, безопасность; Т. 2 - Grigoriev M. G. Mikhail Georgievich (Electrical Engineering and Non-Destructive Testing, 2014)
Заглавие с титульного листа.